Semi-liquefied bamboo modified urea-formaldehyde resin to synthesize composite adhesives. (March 2022) - Pu, Hongxia; Han, Kaixiang; Dai, Rui; Shan, Zhihua
Abstract: Urea-formaldehyde (UF) resin was modified by semi-liquefied bamboo to prepare plywood adhesive. The unliquefied bamboo fiber solid becomes the filler or putty in the bonding process and disperses the UF resin molecules effectively to improve the stability of the UF resin during storage. UF resin was modified by adding 25 wt% semi-liquefied bamboo (SLB) based on UF resin solids. The structure, morphology, thermal stability, rheological behavior and basic properties of the composite adhesives were investigated. The formaldehyde emission of the plywood made with UF containing SLB was lower than that of the plywood made from neat UF, while the modulus of rupture (MOR), modulus of elasticity (MOE) and bonding strength (BS) values increased by increasing the SLB content in the plywood, and the thermal stability of the composite adhesive decreased. The results indicate that the SLB-UF-25% composite adhesive is a good composite adhesive and reaches the national standard technical index of plywood bonding. Graphical abstract: Image 1